Preparation method of iron oxide test sample for powder tabletting-X-ray fluorescence spectrometry and detection method of iron oxide powder
By mixing iron oxide powder with vanadium slag internal control standard samples and grinding and tableting, a test sample of iron oxide with good stability was prepared, and its chemical components were detected by X-ray fluorescence spectroscopy, iron oxide in the prior art was solved The complexity and safety issues of powder detection have achieved high precision, safety and environmental protection detection effects.
Patent Information
- Application Number
- CN202411828996.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to effectively detect chemical components in iron oxide powder, the analysis cycle is long, the operation is complicated, and the use of a large number of harmful chemical reagents is not safe and environmentally friendly.
Using powder tablet-X-ray fluorescence spectroscopy, iron oxide test samples with good stability and high precision were prepared by mixing iron oxide powder with vanadium slag internal control standard samples, and X-ray fluorescence spectroscopy was used. Method to detect iron, silicon, aluminum, manganese and chlorine content in iron oxide powder.
It solves the problems of fluffy, easy cracking and adhesion of iron oxide test samples, improves the accuracy and stability of detection, reduces the use of harmful chemical reagents, and realizes a safe and environmentally friendly detection process.
Smart Images

Figure BDA0005185093670000051 
Figure BDA0005185093670000061 
Figure BDA0005185093670000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of detection technology, in particular to a method for preparing an iron oxide test sample for powder tableting-X-ray fluorescence spectrometry and a method for detecting iron oxide powder. Background Art
[0002] Iron oxide powder is a by-product of the cold rolling pickling line. It is a recycled product of pickled strip steel after roasting and regeneration. It can be used to produce magnetic materials. The chemical components of iron oxide powder for export that need to be routinely tested include total iron, aluminum oxide, silicon dioxide, chlorine, manganese oxide, etc. At present, these five chemical components are measured separately, but the analysis cycle is long, the operation is cumbersome, the function is single, and the efficiency is low. It is increasingly incompatible with modern production management requirements, and a large amount of harmful chemical reagents are used, which is unsafe and environmentally friendly. Domestic steel companies widely use ICP-AES to determine trace components in iron oxide powder. Although the ICP-AES method can determine multiple elements at the same time, it cannot determine the main element iron and the trace component chlorine. At the same time, acid is used to decompose the sample, which is also unsafe and environmentally friendly.
[0003] X-ray fluorescence spectrometry can measure a wide range of elements and concentrations. It is also fast, accurate, easy to operate, and can perform non-destructive analysis. Therefore, X-ray fluorescence spectrometry is widely used in metallurgical analysis, but there are no reports in the literature on its use in the determination of the chemical composition of iron oxide powder.
[0004] X-ray fluorescence spectrometry analysis can be carried out by melting and pressing. The melting method can eliminate the influence of the matrix and the measurement results are accurate. However, the sample of the melting method is highly diluted, and the excitation efficiency of light elements and trace elements is low, the fluorescence yield is low, and they are easily absorbed in the light path, so the measurement results are inaccurate, and the chlorine element is easily lost during the high-temperature melting process. In the pressing method, due to the high viscosity of iron oxide powder and the residual hydrochloric acid contained in it, the sample will adhere firmly to the pressing head if it is directly pressed into a tablet, and it is difficult to peel the sample from the pressing head. If it is peeled off forcefully, it will cause The surface of the sample is delaminated and adhered to the upper surface of the tablet press, causing the sample to be damaged and contaminated with each other. The iron oxide powder is fluffy and no inert agent is added. The sample is thin after tableting and is easy to crack during the molding process. When conducting X-ray fluorescence measurement, the sample is easy to fall off in the vacuum chamber of the X-ray fluorescence spectrometer, causing vacuum chamber contamination. The greater harm is that it causes damage to the beryllium window of the X-ray tube detector and the X-ray fluorescence tube. At the same time, the sample cracks, resulting in distorted test results that are not suitable for powder tableting-X-ray fluorescence spectrometry analysis.
[0005] Therefore, in order to accurately detect the content of components in iron oxide powder, it is of great significance to provide a method for preparing an iron oxide powder test sample and a method for detecting the iron oxide powder sample. Summary of the invention
[0006] The technical problem solved by the present invention is to provide a method for preparing an iron oxide test sample for powder tableting-X-ray fluorescence spectrometry. The iron oxide test sample prepared by the preparation method provided by the present application solves the problem that the iron oxide test sample is fluffy and easy to crack, and has high adhesion and is easy to adhere to the pressure head; the present application also provides a method for detecting the iron, silicon, aluminum, manganese and chlorine contents in iron oxide powder, which has the characteristics of good stability, high precision and high accuracy.
[0007] In view of this, the present application provides a method for preparing an iron oxide test sample for powder tableting-X-ray fluorescence spectrometry, comprising the following steps:
[0008] Mixing iron oxide powder and a vanadium slag internal control standard sample to obtain a mixture;
[0009] The mixture was ground and then tableted to obtain an iron oxide test sample.
[0010] Preferably, the mass ratio of the iron oxide powder to the vanadium slag internal control standard sample is 1:(2-6).
[0011] Preferably, the grinding time is 2 to 10 minutes.
[0012] Preferably, the tabletting pressure is 10 to 30 tons, and the pressure is maintained for 10 to 50 seconds.
[0013] Preferably, the elements in the vanadium slag internal control standard sample include: 5wt% to 10wt% vanadium, 5wt% to 10wt% silicon, 2wt% to 5wt% aluminum, 3wt% to 8wt% manganese, and 20wt% to 40wt% iron.
[0014] The present application also provides a method for detecting the content of iron, silicon, aluminum, manganese and chlorine in iron oxide powder, comprising the following steps:
[0015] Prepare the iron oxide test sample according to the preparation method described;
[0016] The iron oxide test sample is detected by X-ray fluorescence spectrometry to obtain the contents of total iron, aluminum oxide, silicon dioxide, chlorine and manganese oxide in the iron oxide powder.
[0017] Preferably, the X-ray fluorescence spectrometer of the X-ray fluorescence spectrometry is a down-irradiation-scanning spectrometer.
[0018] Preferably, during the detection process, the surface of the iron oxide test sample is covered with a MYLAR film.
[0019] Preferably, the X-ray tube voltage of the X-ray fluorescence spectrometry is 40KV and the tube current is 70mA.
[0020] Preferably, in the X-ray fluorescence spectrometry, the lower limit of detection of SiO2 is 0.014%, and the lower limit of detection of Al2O3 is 0.018%.
[0021] The present application provides a method for preparing an iron oxide test sample for powder tableting-X-ray fluorescence spectrometry, which comprises first mixing iron oxide powder and a vanadium slag internal control standard sample, grinding the obtained mixture and then tableting, thereby obtaining the iron oxide test sample; in the process of preparing the iron oxide test sample, the vanadium slag is used as a diluent and mixed with the iron oxide powder, thereby increasing the density of the sample and reducing the adhesion of the iron oxide test sample, thereby solving the difficult problems of the iron oxide powder being fluffy, difficult to tablet and having high viscosity that affects tableting.
[0022] The present application also provides a method for detecting the iron, silicon, aluminum, manganese and chlorine contents in iron oxide powder, which comprises first preparing an iron oxide test sample, then detecting the iron oxide test sample by X-ray fluorescence spectroscopy, and finally obtaining the contents of total iron, aluminum oxide, silicon dioxide, chlorine and manganese oxide in the iron oxide powder; the method for detecting iron oxide powder provided by the present application, because a vanadium slag diluent is added to the iron oxide powder, and the vanadium slag contains components such as aluminum oxide and silicon dioxide, the X-ray fluorescence intensity of aluminum oxide and silicon dioxide in the iron oxide test sample is increased, the test stability is improved, and the precision and accuracy are guaranteed at the same time. DETAILED DESCRIPTION
[0023] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0024] In view of the problem in the prior art that the iron oxide powder is fluffy and easy to crack after molding, which affects the detection by X-ray fluorescence spectrometry, the present application first prepares an iron oxide test sample, which increases the density of the iron oxide powder and reduces the adhesion of the iron oxide test sample by introducing vanadium slag with uniform and stable composition as a diluent, solves the problem that the iron oxide test sample is fluffy and easy to crack, has high adhesion and is easy to adhere to the pressure head, and ensures the uniformity of the iron oxide test sample, and finally accurately determines the iron, silicon, aluminum, manganese and chlorine content in the iron oxide test sample; Specifically, the embodiment of the present invention discloses a method for preparing an iron oxide test sample for powder tableting-X-ray fluorescence spectrometry, comprising the following steps:
[0025] Mixing iron oxide powder and a vanadium slag internal control standard sample to obtain a mixture;
[0026] The mixture was ground and then tableted to obtain an iron oxide test sample.
[0027] In the process of preparing the iron oxide test sample, the present application first mixes the iron oxide powder and the vanadium slag internal control standard sample to obtain a mixture; the vanadium slag internal control standard sample includes a vanadium slag internal control sample containing vanadium, silicon, aluminum, manganese, iron and other components, and other components of stable inert materials can also be used; the vanadium slag internal control standard sample has stable and uniform components, and the iron oxide powder is iron oxide powder recovered from cold rolling and pickling, which contains total iron, silicon oxide, aluminum oxide, manganese oxide and chlorine. The mass ratio of the iron oxide powder to the vanadium slag internal control standard sample is 1: (2 to 6), specifically, the mass ratio of the iron oxide powder to the vanadium slag internal control standard sample is 1: (3 to 5); for example, the mass ratio of the iron oxide powder to the vanadium slag internal control standard sample is 1: 3, 1: 4 or 1: 5. The mass ratio of the iron oxide powder and the vanadium slag internal control standard sample in the above range can ensure that the obtained iron oxide test sample does not adhere to the tablet press head, and at the same time can improve the detection limit and sensitivity of silicon, aluminum, and manganese in the iron oxide powder; if the ratio is too low, the dilution purpose cannot be achieved, and the mixture of the iron oxide powder and the vanadium slag internal control standard sample will adhere to the tablet press head when pressing the X-ray fluorescence test sample. If the ratio is too high, the accuracy of the iron oxide powder determination is affected. The elements in the vanadium slag internal control standard sample include: vanadium 5wt% to 10wt%, silicon 5wt% to 10wt%, aluminum 2wt% to 5wt%, manganese 3wt% to 8wt%, and iron 20wt% to 40wt%.
[0028] The present application then grinds the mixture and compresses it into tablets to obtain an iron oxide test sample; the grinding time is 2 to 10 minutes, specifically, the grinding time is 4 to 8 minutes; the tableting is a tableting process well known to those skilled in the art, and the present application does not impose any special restrictions on its specific implementation process; in the present application, the tableting is carried out in an MP-35 Shimadzu tablet press, with a pressure of 10 to 30 tons and a pressure maintenance of 10 to 50 seconds; specifically, the tableting pressure is 15 to 25 tons and a pressure maintenance of 15 to 25 seconds.
[0029] The present application also provides a method for detecting the content of iron, silicon, aluminum, manganese and chlorine in iron oxide powder, comprising the following steps:
[0030] Prepare an iron oxide test sample according to the above preparation method;
[0031] The iron oxide test sample is detected by X-ray fluorescence spectrometry to obtain the contents of total iron, aluminum oxide, silicon dioxide, chlorine and manganese oxide in the iron oxide powder.
[0032] In the process of detecting the iron, silicon, aluminum, manganese and chlorine contents in iron oxide powder, the present application firstly prepares an iron oxide test sample, and the preparation method thereof is prepared according to the above method, which will not be elaborated in the present application.
[0033] The present application then uses X-ray fluorescence spectroscopy to detect the iron oxide test sample to obtain the contents of total iron, aluminum oxide, silicon dioxide, chlorine and manganese oxide in the iron oxide.
[0034] In the process of X-ray fluorescence spectrometry detection, the X-ray fluorescence spectrometer used in the X-ray fluorescence spectrometry is a down-irradiation-scanning spectrometer, which can determine all elements, but the X-ray tube is under the sample, so the surface of the iron oxide test sample is covered with a MYLAR film. In the present application, the X-ray tube voltage of the X-ray fluorescence spectrometry is 40KV, and the tube current is 70mA. Since the vanadium slag contains SiO2 and Al2O3, the X-ray fluorescence intensity of the X-ray fluorescence spectrometry for trace components is increased, the test stability is improved, and the detection limits of SiO2 and Al2O3 are reduced, wherein the detection limit of SiO2 is 0.014%, and the detection limit of Al2O3 is 0.018%, further improving the detection accuracy of trace components.
[0035] In the process of detecting the iron, silicon, aluminum, manganese and chlorine contents in iron oxide powder, the present application adopts the vanadium slag dilution-tablet method for determination. Due to the introduction of the vanadium slag internal control standard sample, the prepared iron oxide test sample is representative and easy to prepare, and ultimately the X-ray fluorescence spectrometry analysis has high accuracy, good reproducibility and reproducibility. At the same time, a self-made control sample with a matrix and composition similar to that of the production sample is used to draw a working curve, eliminating the influence of the matrix, and establishing an X-ray fluorescence spectrometry method for determining total iron, aluminum oxide, silicon dioxide, chlorine, manganese oxide and other components in iron oxide powder. The results show that the method has good accuracy and precision, is quick and easy to operate, and is safe and environmentally friendly.
[0036] In order to further understand the present invention, the preparation method of the iron oxide test sample for powder tableting-X-ray fluorescence spectrometry and the detection method of iron oxide powder provided by the present invention are described in detail in combination with the embodiments below. The protection scope of the present invention is not limited by the following embodiments.
[0037] Example
[0038] A) Main instruments and materials
[0039] A1) X-ray spectrometer ARL ADVANT'XP (American Thermoelectric Corporation), X-ray tube voltage 40KV, tube current 70mA, measurement conditions are shown in Table 1;
[0040] Table 1 X-ray spectrometer measurement conditions
[0041]
[0042]
[0043] A2) Pressing machine: MP-35 Shimadzu;
[0044] A3) MYLAR film for X-ray fluorescence spectroscopy, roll, 6μm thick, 92m×76mm;
[0045] A4) Vanadium slag 2# control sample;
[0046] B) Sample determination method
[0047] B1) Preparation of Iron Oxide Test Specimens
[0048] Weigh 5.000g of iron oxide powder and 20.000g of vanadium slag No. 2 control sample in a mortar, mix and grind for 2 minutes, sweep the sample from the mortar wall into the bottom of the mortar, mix and grind for another 2 minutes, take about 13g of the ground sample and put it into the sample ring, press it for 25 seconds under a pressure of 25t to form a smooth and pollution-free disc;
[0049] B2) Sample measurement
[0050] Select the corresponding calibration curve to measure the iron oxide test sample, and the instrument will automatically display the measurement results.
[0051] C) Results and Discussion
[0052] C1) Tablet preparation
[0053] Since iron oxide powder is fluffy and sticky, the sample pressed directly with iron oxide powder is thin and adheres to the pressing head. When peeled off with force, the surface delaminates. To this end, the following experimental studies were carried out:
[0054] C11) Sample and tableting conditions
[0055] Without adding vanadium slag 2# control sample, only the particle size of iron oxide powder was changed, the drying time of iron oxide powder was prolonged, and the pressure and time of tableting were changed. However, the changes of these factors did not improve the adhesion and delamination on the surface of the sample.
[0056] C12) Sample dilution
[0057] Utilization of vanadium slag2 # After a large number of tests, vanadium slag 2 # The control sample and the sample are ground and mixed in a ratio of 4:1 and then pressed into tablets. The surface of the sample is flat and does not adhere to the header, and the effect is good. The vanadium slag 2# control sample is specifically a stable vanadium slag internal control sample containing vanadium, silicon, aluminum, manganese and iron, among which the content of vanadium pentoxide is 16.43wt%, the content of silicon dioxide is 12.68wt%, the content of aluminum trioxide is 3.62wt%, the content of manganese oxide is 7.20wt%, and the content of iron is 31.67wt%;
[0058] C2) Sample dilution uniformity test
[0059] The sample and vanadium slag were put into a mortar in a mass ratio of 1:4, mixed and ground for 2 minutes, the sample from the mortar wall was swept into the bottom of the mortar, mixed and ground for another 2 minutes, and 5 samples were pressed for measurement. The measurement results are shown in Table 2.
[0060] Table 2 Iron oxide test sample dilution uniformity test results (wt%)
[0061]
[0062] It can be seen from Table 2 that the relative standard deviation of the content determination of each component in the iron oxide test sample is below 2.1%. Therefore, the precision of the iron oxide test sample is good, indicating that the iron oxide test sample is mixed more evenly.
[0063] C3) Sample loading before measurement
[0064] The laboratory has two types of X-ray fluorescence spectrometers: upper irradiation and lower irradiation: Shimadzu's upper irradiation-fixed channel, chlorine-free detection channel; American Thermoelectric Company and German Bruker's lower irradiation-scanning channel, which can determine all elements, but the X-ray tube is under the sample, and the powder sample is prone to dust damage to the light tube beryllium window. Therefore, this application preferably uses X-RAY special MYLAR film cut to about 70mm×76mm to cover the sample irradiation surface to prevent dust from falling and damaging the light tube beryllium window;
[0065] C4) Variation of results of repeated determination of chlorine on the same sample
[0066] According to the literature, the chlorine measurement value of the same sample continues to increase with the increase in the number of repeated measurements; there is also information that the change in the repeated measurement value of chlorine is related to the content and existence state. Some samples continue to increase with the increase in the number of measurements, some samples do not change, and for some high-content samples, the chlorine measurement value continues to decrease slightly with the increase in the number of repeated measurements.
[0067] On this basis, this test investigated the effect of repeated determination of samples on chlorine. The determination was repeated 7 times within 4 hours, and the chlorine determination value did not change. The pressed samples were placed in a dryer and measured 3 days later. The low content determination value increased slightly, and the high content did not change. The results are shown in Table 3.
[0068] Table 3 Test results of the influence of the number of measurements on chlorine (wt%)
[0069]
[0070] C5) Calibration curve drawing and detection limit
[0071] C51) Calibration curve drawing
[0072] In order to eliminate the matrix effect, the calibration curve was drawn using the self-made control sample with the same process and matrix as the iron oxide test sample; the retained production samples were collected, and the samples with similar contents were combined into a control sample, which was mixed and fixed, and a total of 7 control samples were prepared, and the content of each component had a certain gradient and covered the measurement range; the control samples were pressed into tablets according to the experimental method, and the X-ray fluorescence intensity was measured under the selected measurement conditions, and the content of each component and the X-ray fluorescence intensity curve were drawn. The results are shown in Table 4;
[0073] Table 4 Calibration curve control sample, calibration curve of each component, and detection limit
[0074]
[0075] The calibration curve shows that the correlation coefficient between the mass fraction of TFe, SiO2, Al2O3, MnO, Cl and other components in iron oxide powder determined by X-ray fluorescence spectrometry and the corresponding X-ray intensity is above 0.9991, indicating a good linear correlation.
[0076] C52) Detection limit and lower detection limit
[0077] The detection limit was set as the content corresponding to 3 times the standard deviation of the background signal fluctuation, and the detection lower limit was set as the content corresponding to 10 times the standard deviation of the background signal fluctuation, and the results were calculated according to formula (1);
[0078]
[0079] Where: LD-detection limit, ug / g;
[0080] m-sensitivity of the measurement, the change in X-ray intensity caused by a 1% change in content (cps / %);
[0081] Ib-background X-ray fluorescence intensity (cps);
[0082] Tb - background measurement time (s).
[0083] The content of SiO2 and Al2O3 in the iron oxide powder sample is low, the X-ray fluorescence intensity is small, and the measurement results fluctuate greatly. Generally, the detection limit of SiO2 and Al2O3 by X-ray fluorescence measurement is above 0.10%. However, this method adds vanadium slag quantitatively. The contents of SiO2 and Al2O3 in the vanadium slag are 0.090% and 0.324%, respectively. The X-ray fluorescence intensity of trace components such as SiO2 and Al2O3 is increased, the measurement stability is improved, and the detection limit is reduced. The detection limits of SiO2 and Al2O3 are 0.014% and 0.018%, respectively.
[0084] C6) Precision test
[0085] A test piece of iron oxide was selected by this experimental method, and the content of each component was measured 10 times under the repeatability condition of this method, and the average value and relative standard deviation of the content of each component were calculated. The relative standard deviation RSD (n=10) of each component was within 2.2, indicating that the method was accurate and good, as shown in Table 5;
[0086] Table 5 Precision test results data table (n = 10, wt%)
[0087]
[0088] C7) Accuracy test
[0089] Ten different batches of iron oxide production samples were selected, and the method provided by this application was used for comparative analysis with the original chemical method, as shown in Table 6;
[0090] Table 6 Comparison test results of different methods (wt%)
[0091]
[0092] As shown in Table 6, the method provided by the present application is consistent with the determination results of each component of the original chemical method. The t-test of paired data shows that the t-statistic value is less than t 临界值 (2.20), indicating that there is no significant difference between the results of the two methods, indicating that the results of this method are accurate and reliable.
[0093] Based on the above research, the following conclusions can be drawn:
[0094] 1) The sample was diluted and tableted with vanadium slag, which not only solved the problem that the iron oxide powder was fluffy and had strong adhesion and could not be directly tableted; MYLAR film was used to cover the irradiated surface of the sample to effectively prevent dust from falling and damaging the beryllium window of the X-ray tube; the calibration curves of each component were drawn with self-made control samples to eliminate the influence of the matrix, and a powder tablet X-ray fluorescence analysis method was established to determine the total iron, aluminum oxide, silicon dioxide, chlorine, manganese oxide and other components in iron oxide powder.
[0095] 2) In the method provided in the present application, components such as alumina and silica are quantitatively added to the vanadium slag, so that the X-ray fluorescence intensity of alumina and silica in the sample is increased, the determination stability is improved, and the detection limit of alumina and silica is reduced from 0.10% to 0.018, thereby expanding the scope of application of the method. The relative standard deviation RSD (n=10) of precision is between 0.1% and 2.2%. The results of 10 batches of samples are consistent with those of the chemical method, with good precision and accuracy. The method has replaced the chemical method for production inspection, and is fast, efficient, green and safe, with good results.
[0096] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0097] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an iron oxide test sample for powder tableting-X-ray fluorescence spectrometry, comprising the following steps: Mixing iron oxide powder and a vanadium slag internal control standard sample to obtain a mixture; The mixture was ground and then tableted to obtain an iron oxide test sample.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the iron oxide powder to the vanadium slag internal control standard sample is 1:(2-6).
3. The preparation method according to claim 1, characterized in that: The grinding time is 2 to 10 minutes.
4. The preparation method according to claim 1, characterized in that: The tabletting pressure is 10-30t, and the pressure is maintained for 10-50s.
5. The preparation method according to claim 1, characterized in that: The elements in the vanadium slag internal control standard sample include: 5wt% to 10wt% of vanadium, 5wt% to 10wt% of silicon, 2wt% to 5wt% of aluminum, 3wt% to 8wt% of manganese, and 20wt% to 40wt% of iron.
6. A method for detecting the content of iron, silicon, aluminum, manganese and chlorine in iron oxide powder, comprising the following steps: Prepare an iron oxide test sample according to the preparation method according to any one of claims 1 to 5; The iron oxide test sample is detected by X-ray fluorescence spectrometry to obtain the contents of total iron, aluminum oxide, silicon dioxide, chlorine and manganese oxide in the iron oxide powder.
7. The detection method according to claim 6, characterized in that: The X-ray fluorescence spectrometer of the X-ray fluorescence spectrometry is a down-irradiation-scanning spectrometer.
8. The detection method according to claim 7, characterized in that: During the detection process, the surface of the iron oxide test sample was covered with a MYLAR film.
9. The detection method according to claim 7, characterized in that: The X-ray tube voltage of the X-ray fluorescence spectrometry is 40 KV, and the tube current is 70 mA.
10. The detection method according to claim 6, characterized in that: In the X-ray fluorescence spectrometry, the lower detection limit of SiO2 is 0.014%, and the lower detection limit of Al2O3 is 0.018%.